Complications of locking and non-locking plate systems in mandibular fractures. Issue 9 (September 2019) - Batbayar, E.-O.; Dijkstra, P.U.; Bos, R.R.M.; van Minnen, B.
Abstract: This systematic review and meta-analysis was performed to critically assess the methodological quality of the existing systematic reviews, and to evaluate the postoperative complications of the mandibular fractures treated with locking and non-locking plate systems. An electronic search was conducted in PubMed, Embase, Web of Science, Cochrane library's electronic databases and grey literate using a combination of Medical Subject Heading terms and key words, until September 2018. No restrictions were applied to the search strategy. In total, three relevant systematic reviews were included, and the quality of these studies was low. A total of 33 studies (20 randomized studies and 13 non-randomized studies) were included in this systematic review, and 16 of them were included in meta-analysis. Most of the included randomized studies had an unclear risk of bias (Cochrane Collaboration); the quality of non-randomized studies ranged between 6 and 17 (Methodological Index for Non-Randomized Studies − MINORS). Based on the results of our meta-analysis, we conclude that locking plates are superior only with respect to the need for mandibulomaxillary fixation (MMF) in the early postoperative period.